Pengaruh Kualitas Produk, Harga, dan Desain Produk terhadap Minat Beli Furniture Custom - Suwardi; Ahmad Dicky Prayoga (Soratekno Publisher, 2026)
The furniture industry is a crucial component of the manufacturing sector and plays a significant role in a country's economy. In Indonesia, the furniture sector has become a promising area with significant potential for economic growth. This industry is showing significant dynamics, primarily due to changing interior design trends, increasing consumer purchasing power, and the development of e-commerce markets that facilitate the distribution of furniture products to various countries. The purpose of this study was to determine the effect of product quality, price, and product design, both partially and simultaneously, on consumer purchasing interest in custom furniture at CV. Podomoro Interior. The analysis method used in this study was quantitative primary data. The testing stages included: validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test, f-test, and coefficient of determination. The data used in this study were collected through a questionnaire, and valid data was collected from 100 respondents. The sampling method used in this study was non-probability sampling using a purposive sampling technique. The testing tool used was SPSS 27. The results showed that product quality, price, and product design had a significant partial and simultaneous influence on purchase intention.